2020
DOI: 10.1017/s1092852920002011
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and autism spectrum: links and risks

Abstract: In the last decades, increasing attention has been provided to socio-cultural and neurobiological factors involved in the psychopathology of feeding and eating disorders (FED), encouraging a multifactorial approach. In this framework, several authors stressed an association between FED and other kinds of psychiatric disorders from both a psychopathological and a neurobiological point of view. In particular, many promising contributions are focusing on the possible link between FED and autism spectrum disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 115 publications
5
53
0
Order By: Relevance
“…Several epidemiological studies, including longitudinal ones, highlighted significant overlaps between AN and ASD diagnoses, while more recently the presence of significant autistic traits was reported also in other Feeding and eating disorders (FED), such as Bulimia nervosa or the emerging condition of Orthorexia nervosa. 3 These findings progressively provided support to the possibility of a re-conceptualization of…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Several epidemiological studies, including longitudinal ones, highlighted significant overlaps between AN and ASD diagnoses, while more recently the presence of significant autistic traits was reported also in other Feeding and eating disorders (FED), such as Bulimia nervosa or the emerging condition of Orthorexia nervosa. 3 These findings progressively provided support to the possibility of a re-conceptualization of…”
mentioning
confidence: 74%
“…Several authors reported possible features of female ASD phenotypes, suggesting that ASD females would focus on different kinds of interests with respect to males, including fictions, celebrities or fashion. 2,3 In addition, ASD females would often show a milder impairment in socio-emotional reciprocity and would be more oriented towards interacting with others, usually adopting camouflaging behaviors in order to cope with social interactions. ASD females would be more aware of their social difficulties and of the need of being, or at least appearing to be, socially integrated: however, the continuous use of camouflaging strategies would result in greater levels of social anxiety, distress and depression, leading to live every relational situation as a performance.…”
mentioning
confidence: 99%
“…Autistic traits were firstly noticed and investigated among parents of children with ASD, leading to the conceptualization of a Broad Autism Phenotype (BAP) [ 6 , 7 ], and further stressing the presence of a continuum between clinical and subthreshold manifestations of the autism spectrum even from a genetic and neurobiological point of view [ 8 , 9 , 10 , 11 , 12 ]. On the other hand, autistic traits have been reported, as highlighted by several studies, not only in first-degree relatives of individuals with ASD, but also in other high-risk groups from the general population and in subjects affected by other psychiatric disorders [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Recent findings stressed the importance of recognizing and addressing autistic traits even with subthreshold due to their possible impact on quality of life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, in line with this hypothesis, highlighted the similarities between AN and ON, stressing that, despite the shift of the focus on food quality rather than food quantity, these conditions would share a common symptomatology core and would also be associated with similar personality traits, such as perfectionism or in exibility [14] [20]. On the other hand, ON has been also associated with other psychopathological dimensions, such as the obsessive-compulsive spectrum, stressing the presence of rituals, repetitive behaviours and perfectionism traits in both the disorders [4].…”
Section: Introductionmentioning
confidence: 91%
“…It was pointed out that the strict focus on food and diet and the ritualized behaviours linked to food intake typical of AN may resemble the pattern of narrow interests and repetitive behaviours of ASD more than the obsessions and compulsion of obsessive-compulsive disorder [14]. In addition to a pattern of rigid habits, in exibility and narrow interests, the presence of de cits in socio-emotional reciprocity and alterations in theory of mind was also reported among AN patients, further stressing its symptomatological overlaps with the autism spectrum [14][23] [24][25]. Several studies in the last years reported, among patients with AN, a higher prevalence of ASD [26].…”
Section: Introductionmentioning
confidence: 99%